Impact of electrophysiological and pharmacological noninducibility following pulmonary vein isolation in patients with paroxysmal and persistent atrial fibrillation. Issue 5 (10th September 2018) - Otsuka, Takayuki; Sagara, Koichi; Arita, Takuto; Yagi, Naoharu; Suzuki, Shinya; Ikeda, Takanori; Yamashita, Takeshi
Abstract: Background: Two methods for testing inducibility of atrial fibrillation (AF)—atrial pacing and isoproterenol infusion—have been proposed to determine the endpoint of catheter ablation. However, the utility of the combination for testing electrophysiological inducibility (EPI) and pharmacological inducibility (PHI) is unclear. Methods: After pulmonary vein isolation (PVI), inducibility of atrial tachyarrhythmia was assessed with the dual methods in 291 consecutive patients with AF (65% paroxysmal) undergoing initial catheter ablation. Results: The incidence of EPI was significantly higher in patients with persistent AF than paroxysmal AF (32.0% vs 11.7%, respectively, P < .001). The incidence of PHI was not significantly different between the two groups (25.2% vs 26.1%, respectively, P = .87). There was no significant difference in AF recurrence according to inducibility in paroxysmal AF. In persistent AF, however, patients achieving neither EPI nor PHI under PVI‐only strategy had significantly lower rates of AF recurrence than those achieving either EPI or PHI and consequently requiring additional ablation for inducible atrial tachyarrhythmia (68.5% vs 49.0%, respectively; log‐rank test, P = .022). In persistent AF, multivariate Cox regression analysis showed that achieving neither EPI nor PHI was a negative independent predictor of AF recurrence (HR 0.492, 95% CI 0.254‐0.916, P = .026). Conclusions: Achieving neither EPI nor PHI following PVI was associated with favorable outcome in patients with persistent AF. The combination of tests may discriminate patients responsive to the PVI‐only strategy. Further selective approaches are necessary to improve outcome for inducible atrial tachyarrhythmia in patients with persistent AF.